Solid-state battery assembly and preparation method thereof
A composite electrolyte layer with fiber-containing layers in solid-state batteries addresses microcracks and short circuits, enhancing electrochemical performance and stability.
Patent Information
- Application Number
- CN202411271868.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-11
- Publication Date
- 2024-12-13
AI Technical Summary
The assembly process of solid-state batteries is prone to microcracks and short circuits due to the complexity of multi-layer stacking, which increases the risk of lithium deposition and reduces energy density, especially affecting the negative electrode.
A solid-state battery assembly with a composite electrolyte layer comprising a first electrolyte layer with an intermediate layer and surrounding layer containing fiber materials, and a second electrolyte layer on at least one side, which prevents microcracks and enhances edge strength to prevent short circuits.
The solution effectively reduces the risk of battery short circuits, improves interface resistance, and enhances electrochemical performance and cycle stability of solid-state batteries.
Smart Images

Figure CN119133628A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium-ion batteries, and in particular relates to a solid-state battery assembly and a preparation method thereof. Background Art
[0002] Currently, lithium-ion batteries are widely used in portable electronics and electric vehicles, and people have higher requirements for the energy density and safety performance of lithium-ion batteries. The energy density of traditional liquid lithium-ion batteries is getting closer and closer to its theoretical upper limit, and its organic flammable electrolyte will bring a series of safety issues.
[0003] In order to solve the safety problems caused by liquid electrolytes, people have begun to pay attention to the development of all-solid-state batteries. All-solid-state batteries are a new generation of power sources composed of solid electrolytes instead of liquid electrolytes. The use of solid electrolytes is expected to further improve the energy of existing lithium-ion batteries. For solid-state batteries, its production process requires breakthroughs in electrodes, electrolytes, interface engineering and packaging technology. The optimization and improvement of production process is an important part of realizing the engineering and commercial application of solid-state batteries.
[0004] At present, the assembly process of the soft pack is to first cold press the positive electrode sheet, the negative electrode sheet and the electrolyte membrane separately, then cold press the electrolyte membrane to the negative electrode sheet, and finally assemble and cold press the positive electrode sheet and the transferred negative electrode sheet. However, in order to prevent the electrolyte membrane from being pressed through and cut by the positive electrode sheet, a 70-100μm thick electrolyte membrane is usually used. This assembly process has a high probability of short circuit and low energy density. This process has the following main problems:
[0005] 1. The operation difficulty increases during the soft-pack multi-layer stacking process. The increase in the number of cold pressing times will not only increase the probability of pole piece contamination, but also make the pole piece brittle after cold pressing. The slight movement during the stacking process may cause micro cracks in the pole piece. The micro cracks in the positive and negative electrodes will not only increase the interface resistance, but also cause lithium deposition and short circuit of the battery, especially the defects in the negative electrode.
[0006] 2. In order to increase the energy density of the battery, the thickness of the electrolyte membrane needs to be reduced, which requires the electrolyte membrane to be strengthened and toughened. Fibers can be added to the slurry of the electrolyte membrane as a whole. The fibers mainly prevent the electrolyte membrane from being cut by the positive electrode, mainly at the edge. The glass fibers in the middle area will reduce the conductivity and interface resistance of the electrolyte membrane.
[0007] Therefore, how to solve the microcrack phenomenon that occurs in the multi-layer stacking process of solid-state batteries and the fibers in the middle area of the electrolyte membrane, thereby reducing the risk of battery short circuit due to lithium deposition, is a technical problem that needs to be studied urgently. Summary of the invention
[0008] In view of the deficiencies of the prior art, the purpose of the present invention is to provide a solid-state battery assembly and a method for preparing the same. The present invention simplifies the stacking structure, constructs a first electrolyte layer by introducing an intermediate layer and a surrounding layer containing fiber materials, and simultaneously arranges a second electrolyte layer on at least one side of the first electrolyte layer, which can effectively avoid microcracks in the pole piece and fiber phenomenon in the electrolyte membrane, improve the interface resistance problem of solid-solid contact, solve the problem of large interface resistance, and especially effectively solve the negative electrode defects, greatly reduce the risk of battery lithium deposition short circuit, significantly improve the electrochemical performance of the solid-state battery, and obtain high initial efficiency and excellent cycle stability.
[0009] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:
[0010] In a first aspect, the present invention provides a solid-state battery assembly, the solid-state battery assembly comprising at least one laminate structure;
[0011] The laminate structure comprises a negative electrode sheet and a positive electrode sheet stacked on at least one side of the negative electrode sheet;
[0012] The laminate structure also includes a composite electrolyte layer, which is arranged between the negative electrode plate and the positive electrode plate. The composite electrolyte layer includes a first electrolyte layer and a second electrolyte layer. The first electrolyte layer includes an intermediate layer and a surrounding layer embedded around the intermediate layer, and the surrounding layer is a U-shaped structure; the surrounding layer contains fiber material; the second electrolyte layer is arranged on at least one side surface of the first electrolyte layer.
[0013] The present invention simplifies the stacking structure, constructs the first electrolyte layer by introducing an intermediate layer and surrounding layers containing fiber materials, and simultaneously arranges a second electrolyte layer on at least one side surface of the first electrolyte layer. This can not only effectively avoid the microcracks of the pole pieces and the fiber phenomenon in the middle area of the electrolyte membrane caused by the complexity of the stacking process, but also improve the interface resistance problem of solid-solid contact, especially the negative electrode defects are effectively solved, and the problem of the positive electrode piece cutting the electrolyte membrane is avoided, which greatly reduces the risk of battery short circuit due to lithium plating, significantly improves the electrochemical performance of solid-state battery components, and obtains high initial efficiency and excellent cycle stability.
[0014] In the present invention, the purpose of providing the composite electrolyte layer is to allow the positive electrode microcracks to self-heal during the lamination process, and the purpose of providing the surrounding layer containing fiber material is to increase the edge strength around the composite double-sided negative electrode sheet to prevent short circuit caused by the positive electrode edge during the assembly test pressurization process.
[0015] It should be noted that the number of laminate structures can be selected according to requirements.
[0016] Those skilled in the art can select appropriate negative electrode materials or positive electrode materials as active materials according to actual needs, which will not be elaborated here.
[0017] It should be noted that the composite electrolyte layer is arranged between the negative electrode sheet and the positive electrode sheet, and the negative electrode sheet side close to the composite electrolyte layer is the negative electrode active layer, and the positive electrode sheet side close to the composite electrolyte layer is the positive electrode active layer.
[0018] Preferably, the material of the composite electrolyte layer includes any one of a sulfide electrolyte, an oxide electrolyte, a halide electrolyte or a polymer electrolyte, or a combination of at least two thereof.
[0019] Preferably, the fiber material includes any one of glass fiber, Kevlar fiber, aromatic polyamide fiber or ceramic fiber, or a combination of at least two thereof.
[0020] In the present invention, fiber doping can significantly improve the mechanical strength of the edge side of the electrolyte layer, preventing the electrolyte from being pressed through and short-circuited during the assembly process under high pressure such as 300 MPa.
[0021] Preferably, the doping amount of the fiber material in the surrounding layer is 7-15wt%, for example, it can be 7wt%, 8wt%, 9wt%, 10wt%, 11wt%, 12wt%, 13wt%, 14wt% or 15wt%.
[0022] Preferably, the thickness of the first electrolyte layer is 4-15 μm, for example, 4 μm, 6 μm, 8 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm or 15 μm.
[0023] Preferably, the cross-sectional width of the surrounding layer is 3-10 mm, for example, 3 mm, 4 mm, 5 mm, 6 mm, 7 mm, 8 mm, 9 mm or 10 mm.
[0024] Preferably, the thickness of the second electrolyte layer is 20-50 μm, for example, 20 μm, 30 μm, 40 μm or 50 μm.
[0025] In the present invention, a second electrolyte layer of a certain thickness is helpful to realize lithium ion conduction. If the thickness of the electrolyte membrane is too thin, the electrolyte membrane process is difficult and the integrity is poor; if the thickness of the electrolyte membrane is too thick, the energy density is reduced.
[0026] Preferably, the material of the second electrolyte layer includes an electrolyte and a binder.
[0027] Preferably, the electrolyte comprises LiPSCl, LiSPSI, LiGePS (Li 10 GeP2S 12), LiSiPS (Li7SiPS8), LiPS (lithium polysulfide), LiSiPSCl (lithium silicon phosphorus sulfonate chloride), LiInCl (Li3InCl6), LiYCl (Li3YCl6), LLGO (lithium lanthanum zirconium oxide) or LLZTO (Li 6.4 Ln3Z 1.4 Ta 0.6 O 12 ) or a combination of at least two of them.
[0028] Preferably, the binder includes any one of SEBS (hydrogenated rubber), SEPS (hydrogenated styrene / isoprene copolymer), PIB (polyisobutylene), NBR (nitrile rubber), HNBR (hydrogenated nitrile), PVDF (polyvinylidene fluoride) or PEO (polyethylene oxide), or a combination of at least two of them.
[0029] Preferably, the solid-state battery assembly includes one laminate structure or at least two laminate structures;
[0030] When the solid-state battery assembly includes a laminate structure, the positive electrode sheet is a single-sided positive electrode sheet, and the negative electrode sheet is a single-sided negative electrode sheet or a double-sided negative electrode sheet;
[0031] When the solid-state battery assembly includes at least two stacked structures, the positive electrode plate located in the middle of the solid-state battery assembly is a double-sided positive electrode plate, and the negative electrode plate located in the middle of the solid-state battery assembly is a double-sided negative electrode plate.
[0032] It should be noted that a single-sided negative electrode sheet refers to a negative electrode sheet that contains a negative electrode active layer on only one surface, a double-sided negative electrode sheet refers to a negative electrode sheet that contains a negative electrode active layer on both surfaces, and the same is true for a double-sided positive electrode sheet.
[0033] In a second aspect, the present invention provides a method for preparing a solid-state battery assembly as described in the first aspect, the preparation method comprising the following steps:
[0034] (a) preparing a negative electrode sheet, a positive electrode sheet and an electrolyte film, and then transferring the electrolyte film onto at least one side of the negative electrode sheet and / or the positive electrode sheet to obtain a second electrolyte layer;
[0035] (b) coating a source layer on at least one side surface of the positive electrode sheet after the treatment in step (a) or on the middle area of at least one side surface of the negative electrode sheet after the treatment in step (a), and coating a peripheral layer with a U-shaped structure on the edge area of at least one side surface of the negative electrode sheet, the source layer and the peripheral layer are embedded to form a first electrolyte layer, the first electrolyte layer includes an intermediate layer and a peripheral layer embedded around the intermediate layer, to obtain a laminate structure with interface fusion and no cracks;
[0036] Wherein, the surrounding layers contain fiber materials;
[0037] (c) Repeat steps (a) and (b) at least once, and then stack the at least one laminate structure obtained, and then perform cold pressing to obtain the solid-state battery assembly.
[0038] Preferably, the method for transferring the electrolyte membrane in step (a) comprises: laminating the electrolyte membrane on at least one side surface of the positive electrode sheet or the negative electrode sheet, and then performing a cold pressing process.
[0039] Preferably, during the transfer process of the electrolyte membrane, the cold pressing pressure of the cold pressing treatment is 300-600MPa, such as 300MPa, 400MPa, 500MPa or 600MPa, and the holding time is 5-20min, such as 5min, 10min, 15min or 20min.
[0040] Preferably, the coating method of the source layer or the surrounding layer in step (b) independently includes any one of a spraying method, a dispensing method or a screen printing method. The present invention adopts the method of spraying, dispensing or screen printing to make the microcracks on the surface of the pole piece fuse and heal themselves, which can effectively avoid the generation of microcracks, improve the interface resistance problem of solid-solid contact, and significantly improve the battery performance.
[0041] It should be noted that during the spraying preparation process of the surrounding layer, a baffle is required to cover the middle area of the negative electrode plate, so as to achieve the preparation of the surrounding layer of the U-shaped structure.
[0042] Preferably, the thickness of the source layer in step (b) is 1-10 μm, for example, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm or 10 μm.
[0043] Preferably, the cold pressing pressure of the cold pressing treatment in step (c) is 300-600 MPa, for example, 300 MPa, 400 MPa, 500 MPa or 600 MPa.
[0044] Preferably, the holding time of the cold pressing treatment in step (c) is 5-20 min, for example, 5 min, 10 min, 15 min or 20 min.
[0045] Preferably, the preparation method comprises the following steps:
[0046] (1) Adopting a transfer method, laminating an electrolyte membrane with a thickness of 20-50 μm on at least one side surface of a negative electrode sheet or a positive electrode sheet, and then cold pressing treatment is performed at a cold pressing pressure of 300-600 MPa for 5-20 min to obtain a negative electrode sheet or a positive electrode sheet having a second electrolyte layer, and then coating an intermediate layer on at least one side surface of the positive electrode sheet or in the middle area of at least one side surface of the negative electrode sheet, and coating a peripheral layer of a U-shaped structure on the edge area of at least one side surface of the negative electrode sheet, and the intermediate layer and the peripheral layer are embedded to form a first electrolyte layer, thereby obtaining a laminate structure with an interface fusion and no cracks;
[0047] Wherein, the material of the electrolyte membrane includes an electrolyte and a binder, the electrolyte includes any one of LiPSCl, LiSPSI, LiGePS, LiSiPS, LiPS, LiSiPSCl, LiInCl, LiYCl, LLGO or LZTO or a combination of at least two, the binder includes any one of SEBS, SEPS, PIB, NBR, HNBR, PVDF or PEO or a combination of at least two; the material of the first electrolyte layer includes any one of a sulfide electrolyte, an oxide electrolyte, a halide electrolyte or a polymer electrolyte or a combination of at least two, and the surrounding layer also contains a fiber material;
[0048] (2) When step (1) is performed only once, the laminate structure in step (1) is a single cell, the positive electrode sheet is a single-sided positive electrode sheet, and the negative electrode sheet is a single-sided negative electrode sheet or a double-sided negative electrode sheet; or
[0049] When step (1) is repeated at least twice, a stacked structure is used as a unit, and the obtained multiple units are stacked to construct a stacked battery, wherein the positive electrode sheet located in the middle of the stacked battery is a double-sided positive electrode sheet, and the negative electrode sheet located in the middle of the stacked battery is a double-sided negative electrode sheet;
[0050] (3) Drying the single cell or stacked cell obtained in step (2) at a temperature of 50-100°C for 30 min-2 h, and then cold pressing the single cell or stacked cell at a pressure of 300-600 MPa for 5-20 min to obtain the solid-state battery assembly.
[0051] The numerical range described in the present invention not only includes the point values listed above, but also includes any point values between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0052] Compared with the prior art, the present invention has the following beneficial effects:
[0053] The present invention simplifies the stacking structure, can effectively avoid micro cracks in the pole pieces caused by the complex stacking process, improves the interface resistance problem of solid-solid contact, and especially effectively solves the negative electrode defects, greatly reduces the risk of battery lithium plating short circuit, significantly improves the electrochemical performance of solid-state battery components, and obtains high initial efficiency and excellent cycle stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0054] Figure 1 This is a schematic diagram of the structure of the solid-state battery assembly provided in Example 1 of the present invention.
[0055] Figure 2 This is a flow chart of preparing the first electrolyte layer in Example 2 of the present invention.
[0056] Among them, 1-positive electrode plate; 2-intermediate layer; 21-source layer; 3-surrounding layer; 4-second electrolyte layer; 5-negative electrode plate. DETAILED DESCRIPTION
[0057] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0058] It should be noted that the positive electrode described below uses NCM811 system material with a surface loading of 25 mg / cm 2 , the negative electrode adopts silicon-based system materials.
[0059] Example 1
[0060] This embodiment provides a solid-state battery assembly, and its structural schematic diagram is as follows Figure 1 As shown, it is composed of a laminate structure, and the laminate structure is recorded as a single cell;
[0061] The single cell comprises a positive electrode sheet 1, a composite electrolyte layer and a negative electrode sheet 5 which are stacked in sequence;
[0062] The positive electrode sheet 1 is a single-sided positive electrode sheet, and the negative electrode sheet 5 is a single-sided negative electrode sheet; the cross-sectional width of the negative electrode sheet 5 is greater than the cross-sectional width of the positive electrode sheet 1;
[0063] The composite electrolyte layer is stacked in sequence along a direction away from the positive electrode plate 1, wherein the first electrolyte layer comprises an intermediate layer 2 and a surrounding layer 3 embedded around the intermediate layer 2, wherein the surrounding layer 3 is a U-shaped structure; the surrounding layer 3 contains fiber material, wherein the doping amount of the fiber material in the surrounding layer 3 is 12wt%, and the fiber material is glass fiber;
[0064] The thickness of the first electrolyte layer is 10 μm, the composite electrolyte layer includes a sulfide electrolyte, and the sulfide electrolyte is LiPSCl; the cross-sectional width of the intermediate layer 2 is 4 mm; the area of the first electrolyte layer is the same as the area of the negative electrode plate;
[0065] The thickness of the second electrolyte layer 4 is 50 μm, and the material of the second electrolyte layer 4 includes LiPSCl and SEBS in a mass ratio of 98:2.
[0066] This embodiment also provides a method for preparing the above-mentioned solid-state battery assembly, and the preparation method comprises the following steps:
[0067] (1) a single-sided negative electrode sheet and a single-sided positive electrode sheet were prepared respectively by a conventional wet coating process, and then a prepared electrolyte membrane was bonded to the active layer surface of the single-sided negative electrode sheet by a transfer method, and then a cold pressing treatment was performed at a cold pressing pressure of 450 MPa for 12 minutes to obtain a negative electrode sheet with a second electrolyte layer;
[0068] Then, the electrolyte slurry for constructing the source layer is sprayed on the middle area of the single-sided surface of the negative electrode plate by a spraying method, and the electrolyte slurry for constructing the surrounding layer is sprayed on the edge area. After the source layer with a thickness of 10 μm and the surrounding layer with a thickness of 10 μm are embedded, the edge part of the source layer and the surrounding layer are fused into one, and the source layer and the surrounding layer are fused with the surface of the positive electrode plate to form a first electrolyte layer. At this time, the first electrolyte layer includes the middle layer and the surrounding layer embedded around the middle layer, and a laminate structure with interface fusion and no cracks is obtained, that is, a single cell;
[0069] Among them, the material of the second electrolyte layer includes an electrolyte and a binder with a mass ratio of 98:2, the electrolyte is LiPSCl, and the binder is SEBS; the electrolyte slurry for constructing the source layer includes an electrolyte, a solvent and a binder, with a solid content of 40%, the electrolyte is LiPSCl, the binder is SEBS, the mass ratio of the electrolyte and the binder is 98:2, and the solvent is toluene; the electrolyte slurry for constructing the surrounding layer includes an electrolyte, a fiber material, a solvent and a binder, the electrolyte is LiPSCl, the binder is SEBS, the mass ratio of the electrolyte and the binder is 98:2, the solvent is toluene, the fiber material is glass fiber, and the doping amount is 12wt%;
[0070] (2) Drying the single battery obtained in step (1) at a temperature of 60° C. for 30 min, and then cold pressing the single battery at a pressure of 450 MPa for 12 min to obtain the solid-state battery assembly.
[0071] Example 2
[0072] This embodiment provides a solid-state battery assembly, the solid-state battery assembly is composed of a stacked structure, and the stacked structure is recorded as a single cell;
[0073] The single cell comprises a negative electrode sheet, and a composite electrolyte layer and a positive electrode sheet stacked on both sides of the negative electrode sheet;
[0074] The positive electrode sheet is a single-sided positive electrode sheet, and the negative electrode sheet is a double-sided negative electrode sheet; the cross-sectional width of the negative electrode sheet is greater than the cross-sectional width of the positive electrode sheet;
[0075] The composite electrolyte layer is stacked in sequence along a direction away from the positive electrode sheet, wherein the first electrolyte layer comprises an intermediate layer and a surrounding layer embedded around the intermediate layer, wherein the surrounding layer is a U-shaped structure; the surrounding layer contains fiber material, wherein the doping amount of the fiber material in the surrounding layer is 7wt%, and the fiber material is Kevlar fiber;
[0076] The thickness of the first electrolyte layer is 12 μm, and the first electrolyte layer includes a sulfide electrolyte, and the sulfide electrolyte is LiInCl; the cross-sectional width of the intermediate layer is 5 mm; the area of the first electrolyte layer is the same as the area of the negative electrode plate;
[0077] The thickness of the second electrolyte layer is 30 μm, and the material of the second electrolyte layer includes LiInCl and HNBR in a mass ratio of 97:3.
[0078] This embodiment also provides a method for preparing the above-mentioned solid-state battery assembly, and the preparation method comprises the following steps:
[0079] (1) A double-sided negative electrode sheet and two single-sided positive electrode sheets were prepared by a conventional wet coating process, and then a layer of prepared electrolyte membrane was attached to both sides of the double-sided negative electrode sheet by a transfer method, and then a cold pressing process was performed at a cold pressing pressure of 450 MPa for 12 minutes to obtain a double-sided negative electrode sheet with a second electrolyte layer, and then the double-sided negative electrode sheet was subjected to a cold pressing process as follows: Figure 2The process flow shown in the figure adopts a spraying method to spray the electrolyte slurry for constructing the surrounding layer 3 on the edge area of the surface of the second electrolyte layer 4 on both sides of the double-sided negative electrode sheet to form the surrounding layer 3 of the U-shaped structure, and sprays the electrolyte slurry for constructing the source layer 21 on the surface of the active layer of the single-sided positive electrode sheet, and then after the source layer 21 with a thickness of 8 μm and the surrounding layer 3 with a thickness of 12 μm are embedded, the edge part of the source layer 21 and the surrounding layer 3 are fused into one, and the source layer 21 and the surrounding layer are fused with the surface of the second electrolyte layer 4 of the double-sided negative electrode sheet to form a first electrolyte layer with a thickness of 12 μm. At this time, the first electrolyte layer includes the intermediate layer 2 and the surrounding layer 3 embedded around the intermediate layer 2, and a laminate structure with interface fusion and no cracks is obtained, that is, a single cell;
[0080] The material of the second electrolyte layer includes an electrolyte and a binder in a mass ratio of 97:3, the electrolyte is LiInCl, and the binder is HNBR; the electrolyte slurry for constructing the source layer includes an electrolyte, a solvent and a binder, with a solid content of 37%, the electrolyte is LiInCl, the binder is HNBR, the mass ratio of the electrolyte and the binder is 98:2, and the solvent is n-heptane; the electrolyte slurry for constructing the surrounding layer includes an electrolyte, a solvent and a binder, with a solid content of 37%, the electrolyte is LiInCl, the binder is HNBR, the mass ratio of the electrolyte and the binder is 98:2, the solvent is n-heptane, and the fiber material is Kevlar fiber with a doping amount of 7wt%;
[0081] (2) Drying the single battery obtained in step (1) at a temperature of 50° C. for 1 h, and then cold pressing the single battery at a pressure of 450 MPa for 12 min to obtain a solid-state battery assembly.
[0082] Example 3
[0083] The difference between this embodiment and embodiment 1 is that the preparation methods of the middle layer and the surrounding layers are both screen printing, and the cold pressing pressure in step (1) is 300 MPa, and the cold pressing treatment time is 20 minutes.
[0084] The rest of the preparation methods and parameters were the same as those in Example 1.
[0085] Example 4
[0086] The difference between this embodiment and embodiment 2 is that the preparation of the middle layer and the surrounding layers is both carried out by dispensing, and the cold pressing pressure in step (1) is 600 MPa, and the cold pressing treatment time is 5 minutes.
[0087] The rest of the preparation methods and parameters were the same as those in Example 2.
[0088] Example 5
[0089] The difference between this embodiment and embodiment 1 is that the cold pressing pressure in step (2) is 300 MPa and the cold pressing treatment time is 20 min.
[0090] The rest of the preparation methods and parameters were the same as those in Example 1.
[0091] Example 6
[0092] The difference between this embodiment and embodiment 2 is that the cold pressing pressure in step (2) is 600 MPa and the cold pressing treatment time is 5 minutes.
[0093] The rest of the preparation methods and parameters were the same as those in Example 2.
[0094] Example 7
[0095] The difference between this embodiment and embodiment 1 is that the fiber material doped in the electrolyte slurry for constructing the surrounding layer in step (1) is aromatic polyamide fiber, and the doping amount is 15 wt%.
[0096] The rest of the preparation methods and parameters were the same as those in Example 1.
[0097] Comparative Example 1
[0098] The difference between this comparative example and Example 1 is that the first electrolyte layer formed by the middle layer and the surrounding layer is not provided, that is, the electrolyte slurry for constructing the source layer and the electrolyte slurry for constructing the surrounding layer are not sprayed on the surface of the negative electrode plate in step (1).
[0099] The rest of the preparation methods and parameters were the same as those in Example 1.
[0100] Comparative Example 2
[0101] The difference between this comparative example and Example 1 is that no second electrolyte layer is provided, that is, the bonding of the electrolyte membrane in step (1) is not performed.
[0102] The rest of the preparation methods and parameters were the same as those in Example 1.
[0103] Comparative Example 3
[0104] The difference between this embodiment and embodiment 1 is that no glass fiber is added to the electrolyte slurry for constructing the surrounding layer in step (1).
[0105] The rest of the preparation methods and parameters were the same as those in Example 1.
[0106] Comparative Example 4
[0107] This comparative example provides a method for preparing a solid-state battery assembly, the preparation method comprising the following steps:
[0108] After the positive electrode sheet, the negative electrode sheet and the electrolyte membrane are cold pressed separately, the electrolyte membrane is then cold-pressed and transferred to the negative electrode sheet. Finally, the positive electrode sheet and the transferred negative electrode are assembled and cold-pressed.
[0109] Performance Testing
[0110] The solid-state battery components provided in the above embodiments and comparative examples were subjected to electrochemical performance tests, including first efficiency and cycle stability.
[0111] The first effective test conditions: the solid-state battery assembly was subjected to an electrochemical test of 0.05C charge and discharge at a temperature of 45°C.
[0112] Cycle stability test conditions: After the first cycle test, an electrochemical test of 0.1C charge / 0.5C discharge is performed.
[0113] The test results are shown in Table 1.
[0114] Table 1
[0115]
[0116] analyze:
[0117] It can be seen from the above table that the preparation method provided by the present invention simplifies the lamination process, can effectively avoid micro cracks in the pole pieces caused by the complexity of the lamination process, while reducing the thickness, strengthening and toughening the electrolyte membrane, avoiding the influence of the glass fiber in the middle layer on the interface resistance, thereby improving the energy density of the battery, improving the interface resistance problem of solid-solid contact, greatly reducing the risk of battery short circuit due to lithium plating, significantly improving the electrochemical performance of solid-state battery components, and obtaining high initial efficiency and excellent cycle stability.
[0118] It can be seen from Example 1 and Comparative Example 1 that if the first electrolyte layer formed by the middle layer and the surrounding layers is not provided, micro cracks will appear in the pole piece, thereby causing a short circuit in the battery.
[0119] It can be seen from Example 1 and Comparative Example 2 that if the second electrolyte layer is not provided, the electrolyte will be pressed through by the positive electrode, thereby causing a short circuit in the battery.
[0120] It can be seen from Examples 1 and 3 that if glass fiber is not added to the electrolyte slurry for constructing the surrounding layer in step (1), the electrolyte will be pressed through by the positive electrode, thereby causing a short circuit in the battery.
[0121] It can be seen from Example 1 and Comparative Example 4 that if the preparation method described in Comparative Example 4 is adopted, micro cracks will appear in the electrode piece, thereby causing a short circuit in the battery.
[0122] The applicant declares that the present invention illustrates the process method of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned process steps, that is, it does not mean that the present invention must rely on the above-mentioned process steps to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of the raw materials selected by the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A solid-state battery assembly, characterized in that: The solid-state battery assembly includes at least one stacked structure; The laminate structure comprises a negative electrode sheet and a positive electrode sheet stacked on at least one side of the negative electrode sheet; The laminate structure also includes a composite electrolyte layer, which is arranged between the negative electrode plate and the positive electrode plate. The composite electrolyte layer includes a first electrolyte layer and a second electrolyte layer. The first electrolyte layer includes an intermediate layer and a surrounding layer embedded around the intermediate layer, and the surrounding layer is a U-shaped structure; the surrounding layer contains fiber material; the second electrolyte layer is arranged on at least one side surface of the first electrolyte layer.
2. The solid-state battery assembly according to claim 1, characterized in that: The material of the composite electrolyte layer includes any one of a sulfide electrolyte, an oxide electrolyte, a halide electrolyte or a polymer electrolyte, or a combination of at least two thereof; Preferably, the fiber material comprises any one of glass fiber, Kevlar fiber, aromatic polyamide fiber or ceramic fiber, or a combination of at least two thereof; Preferably, the doping amount of the fiber material in the surrounding layer is 7-15wt%; Preferably, the thickness of the first electrolyte layer is 4-15 μm; Preferably, the cross-sectional width of the surrounding layer is 3-10 mm.
3. The solid-state battery assembly according to claim 1 or 2, characterized in that: The thickness of the second electrolyte layer is 20-50 μm; Preferably, the material of the second electrolyte layer includes an electrolyte and a binder; Preferably, the electrolyte comprises any one or a combination of at least two of LiPSCl, LiSPSI, LiGePS, LiSiPS, LiPS, LiSiPSCl, LiInCl, LiYCl, LLGO or LLZTO; Preferably, the binder includes any one of SEBS, SEPS, PIB, NBR, HNBR, PVDF or PEO, or a combination of at least two thereof.
4. The solid-state battery assembly according to any one of claims 1 to 3, characterized in that: The solid-state battery assembly includes one laminate structure or at least two laminate structures; When the solid-state battery assembly includes a laminate structure, the positive electrode sheet is a single-sided positive electrode sheet, and the negative electrode sheet is a single-sided negative electrode sheet or a double-sided negative electrode sheet; When the solid-state battery assembly includes at least two stacked structures, the positive electrode plate located in the middle of the solid-state battery assembly is a double-sided positive electrode plate, and the negative electrode plate located in the middle of the solid-state battery assembly is a double-sided negative electrode plate.
5. A method for preparing a solid-state battery assembly according to any one of claims 1 to 4, characterized in that: The preparation method comprises the following steps: (a) preparing a negative electrode sheet, a positive electrode sheet and an electrolyte film, and then transferring the electrolyte film onto at least one side of the negative electrode sheet and / or the positive electrode sheet to obtain a second electrolyte layer; (b) coating a source layer on at least one side surface of the positive electrode sheet after the treatment in step (a) or on the middle area of at least one side surface of the negative electrode sheet after the treatment in step (a), and coating a peripheral layer with a U-shaped structure on the edge area of at least one side surface of the negative electrode sheet, the source layer and the peripheral layer are embedded to form a first electrolyte layer, the first electrolyte layer includes an intermediate layer and a peripheral layer embedded around the intermediate layer, to obtain a laminate structure with interface fusion and no cracks; Wherein, the surrounding layers contain fiber materials; (c) Repeat steps (a) and (b) at least once, and then stack the at least one laminate structure obtained, and then perform cold pressing to obtain the solid-state battery assembly.
6. The preparation method according to claim 5, characterized in that: The method for transferring the electrolyte membrane in step (a) comprises: laminating the electrolyte membrane on at least one side surface of the positive electrode sheet or the negative electrode sheet, and then performing a cold pressing process.
7. The preparation method according to claim 6, characterized in that: During the transfer process of the electrolyte membrane, the cold pressing pressure of the cold pressing treatment is 300-600 MPa, and the pressure holding time is 5-20 min.
8. The preparation method according to any one of claims 5 to 7, characterized in that: The coating methods of the source layer and the surrounding layer in step (b) independently include any one of a spraying method, a dispensing method or a screen printing method; Preferably, the thickness of the source layer in step (b) is 1-10 μm.
9. The preparation method according to any one of claims 5 to 8, characterized in that: The cold pressing pressure of the cold pressing treatment in step (c) is 300-600 MPa; Preferably, the holding time of the cold pressing treatment in step (c) is 5-20 minutes.
10. The preparation method according to any one of claims 5 to 9, characterized in that: The preparation method comprises the following steps: (1) Adopting a transfer method, laminating an electrolyte membrane with a thickness of 20-50 μm on at least one side surface of a negative electrode sheet or a positive electrode sheet, and then cold pressing treatment is performed at a cold pressing pressure of 300-600 MPa for 5-20 min to obtain a negative electrode sheet or a positive electrode sheet having a second electrolyte layer, and then coating an intermediate layer on at least one side surface of the positive electrode sheet or in the middle area of at least one side surface of the negative electrode sheet, and coating a peripheral layer of a U-shaped structure on the edge area of at least one side surface of the negative electrode sheet, and the intermediate layer and the peripheral layer are embedded to form a first electrolyte layer, thereby obtaining a laminate structure with an interface fusion and no cracks; Wherein, the material of the electrolyte membrane includes an electrolyte and a binder, the electrolyte includes any one of LiPSCl, LiSPSI, LiGePS, LiSiPS, LiPS, LiSiPSCl, LiInCl, LiYCl, LLGO or LZTO or a combination of at least two, the binder includes any one of SEBS, SEPS, PIB, NBR, HNBR, PVDF or PEO or a combination of at least two; the material of the first electrolyte layer includes any one of a sulfide electrolyte, an oxide electrolyte, a halide electrolyte or a polymer electrolyte or a combination of at least two, and the surrounding layer also contains a fiber material; (2) When step (1) is performed only once, the laminate structure in step (1) is a single cell, the positive electrode sheet is a single-sided positive electrode sheet, and the negative electrode sheet is a single-sided negative electrode sheet or a double-sided negative electrode sheet; or When step (1) is repeated at least twice, a stacked structure is used as a unit, and the obtained multiple units are stacked to construct a stacked battery, wherein the positive electrode sheet located in the middle of the stacked battery is a double-sided positive electrode sheet, and the negative electrode sheet located in the middle of the stacked battery is a double-sided negative electrode sheet; (3) Drying the single cell or stacked cell obtained in step (2) at a temperature of 50-100°C for 30 min-2 h, and then cold pressing the single cell or stacked cell at a pressure of 300-600 MPa for 5-20 min to obtain the solid-state battery assembly.
